Montgomery's Federal Taxes (Book). - Smith, Frank P.; Austin, James R. (The Accounting Review, 1949)
Abstract Reviews the book "Montgomery's Federal Taxes-Corporations and Partnerships 1947-48," by Robert H. Montgomery, Conrad B. Taylor and Mark E. Richardson.